Exploring the Relationship Between Tourism Development and Employment Generation in Nepal - Kadayat, Giri Raj (Journal of Durgalaxmi, 2024)
This study explores the relationship between tourism development and employment generation in Nepal using time-series data from 2000 to 2019. Key tourism indicators such as international tourist arrivals, tourism receipts, and tourism investments were analyzed using regression models and Granger causality tests. The results reveal a strong positive impact of tourist arrivals and receipts on employment, while tourism investments showed limited significance. The findings emphasize tourism's role in job creation and its spillover effects on the broader economy. Policy recommendations include infrastructure development, skill training, sustainable tourism practices, and targeted investments to maximize tourism’s potential for inclusive growth.